PREPARASI DAN KARAKTERISASI KATALIS BERBASIS LOGAM Ni, Co DAN Mo YANG DIEMBANKAN PADA ULTRA STABLE Y-ZEOLITE (USY) UNTUK HIDRODESULFURISASI TIOFEN - , Khoirina Dwi N., S.Si.,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research deals with preparing and characterizing the metal based-catalyst of Ni, Co and Mo supported on Ultra Stable Y-zeolite (USY) and, is aimed to ascertain the best produced catalyst for hydrodesulfulization (HDS) reaction of thiophene. Preparation, activation and characterization were done. Monometal catalyst (Ni/USY and Mo/USY) was prepared by applying 2, 6, 10 and 14% wt of salt metal precursor concentration. The bimetal one (Ni, Mo)/USY was prepared according to the coimpregnation and sequential impregnation method. Here, the given concentration of Ni are 2, 4, 6, and 8 % wt, at the constant concentration of Mo 8 % wt. The produced catalysts were activated trough calcination, oxidation and reduction and, were characterized as according to the data of XRD, AAS, acidity, surface area and porosity. The best value of acidity of the activated (Ni, Mo)/USY resulted from particular combination of treatment and concentration was reffered for the (Co, Mo)/USY preparation. All best catalysts were tested in the HDS reaction of tiophene under temperature of 200-400ÂºC, H2 flow rate of 2.5-8.85 mL/min and the ToS of 15-75 minutes. The results of GC and GC-MS were scrutinized to determine the best catalytic activity (%) that was defined as the amount of butene product per metal content in a mol. The result showed that the best catalyst was MoNi2/USY, a catalyst produced from sequential impregnation where the Mo was impregnated at first followed by 2% wt of Ni. This catalyst gave result to the activity of 17.6 % at temperature of 350 ÂºC, H2 flow rate of 5 mL/min and ToS of 45 minutes. Hydrogenation was the first reaction to occur followed by desulfurization.